The effect of brain breaks on participation motives, attitudes, cognitive function and physical activity behaviour among trainee teachers in Kuching, Sarawak - Yi, Ting Pei (2023)
Brain-breaks are short mental physical breaks incorporated periodically and can help to stimulate one’s health and motivation. The purposes of the study are to (1) examine the effect of brain-breaks on participation motives, attitudes and cognitive functions among the Sarawak’s trainee teachers (study one). In addition, this study also aims to (2) examine the effect of brain-breaks on physical activity behaviours among the Sarawak’s trainee teachers (study two). During study one, the brain-breaks were conducted twice a day, and five times a week for a duration of 12 weeks. The participants comprised of 48 trainee teachers (24 males and 24 females) aged 18 and 19 years old randomly divided into intervention (n = 24) and control group (n = 24). The Physical Activity and Leisure Motivation Scale (PALMS), Attitude towards Physical Activity Scale (APAS), MUSE headband and the BC-541 Tanita Inner Scan Body Composition Monitor were utilised. Independent t-test and mixed factorial ANOVA were used to analyse the data. During study two, a total of 12 trainee teachers were recruited from both Institute of Teacher Campuses. They were randomly assigned into two groups (gender matched) which were the control group (n = 6) and intervention group (n = 6). The Mi Band 4 was used to access the participants’ physical activity through brain-breaks. Descriptive analysis, qualitative method of enquiry and interview were conducted at the end of the study. For study one, mixed factorial ANOVA for APAS variables revealed significant time effect for self-efficacy, F(1, 46) = 7.20, p-value (ηp2) = .010 (.135). The mixed factorial ANOVA for PALMS variables revealed significant time effect for; competition/ego, F(1, 46) = 10.82, p-value (ηp2) = .002 (.019); other’s expectations, F(1, 46) = 11.05, p-value (ηp2) = .002 (.204) and enjoyment, F(1, 46) = 6.64, p-value (ηp2) = .013 (.130). In addition, enjoyment, F(1, 46) = 6.64, p-value (ηp2) = .013 (.130) was also significant for group effect. Mixed factorial ANOVA for anthropometric body composition variables showed significant time effect for body fat percentage, F(1, 46) = 5.46, p-value (ηp2) = .024 (.106); together with significant interaction effect for muscle mass, F(1, 46) = 5.80, p-value (ηp2) = .020 (.112); bone mass F(1, 46) = 6.66, p-value (ηp2) = .013 (.127) and basal metabolic rate F(1, 46) = 7.15, p-value (ηp2) = .010 (.135). For study 2, participants had also showed positive responses for the three-open ended questions. The positive phrases revealed by the participants showed that brain-breaks increased their level of motivation and focus as well as improved their learning progress. The results revealed that brain-breaks were successful in improving the motivation and attitudes towards physical activity; increased real time physical activity behaviour. Thus, brain-breaks should be recommended to be used throughout the higher education campuses in Malaysia.